Physical sulfate attack on concrete lining–A field case analysis. (June 2017) - Liu, Zanqun; Zhang, Fengyan; Deng, Dehua; Xie, Youjun; Long, Guangcheng; Tang, Xuguang
Abstract: In the tunnels of the Cheng-Kun Railway in China, concrete failure can usually be observed from the effect of sulfates. A field investigation was conducted to analyze the concrete damage mechanism by means of XRD, IC, AAS and EPMA. The results showed that (1) large amounts of Na2 SO4 were generated on the surface layer of the concrete lining, causing concrete detachment layer by layer; (2) the concrete lining in contact with air had been neutralized to more than 50 mm in depth, and the cement hydration products had been converted into CaCO3 ; (3) ettringite and gypsum, the products of chemical sulfate attack, were also detected in the neutralized concrete lining. This analysis of a field case concluded that Na2 SO4 crystallization caused the detachment of the surface layer of the concrete lining, and the chemical sulfate attack occurred in the inner part of the concrete lining.